"Tetramethylsilanoviologen": Synthesis, characterization, and hydrolysis of a Silolodipyridinium ion. (5th September 2017) - Lee, David A.; Peloquin, Derek M.; Yapi, Edi W.; McMinn, Lucas A.; Merkert, Jon W.; Donovan-Merkert, Bernadette T.; Vitallo, Ashley Ariel; Peterson, Ashley R.; Jones, Daniel S.; Ceccarelli, Christopher; Schmedake, Thomas A.
Graphical abstract: A silicon-bridged viologen has been synthesized by methylation of 4, 4′-dipyridinodimethylsilole. The dicationic species emits at 360 nm and exhibits two chemically reversible one electron reduction waves. The silanoviologen is susceptible to ring-opening hydrolysis. Abstract: A silicon-bridged viologen has been synthesized by methylation of 4, 4′-dipyridinodimethylsilole, and represents a new addition to the growing family of heteroatom bridged viologens. The dicationic species emits at 360 nm and exhibits two chemically reversible one electron reduction waves in acetonitrile at E1/2 ​(2+/1+) = −0.829 V and E1/2 ​(1+/0) = −1.307 V (versus Fc/Fc + ). The UV–Vis spectrum for each of the three charge states is similar to the corresponding unbridged methyl viologen species. The silanoviologen is susceptible to ring-opening hydrolysis.